Tissue engineering meniscus stent for minimally invasive suture-free implantation surgery as well as preparation method and application of tissue engineering meniscus stent
By adopting elastomer/hydrogel composite meniscus stents in the field of tissue engineering meniscus, the problems of poor mechanical properties of hydrogels and instability of porous structures are solved, and minimally invasive suture-free implantation is achieved through shape memory and strong adhesion functions, reducing surgical trauma and recovery time.
Patent Information
- Application Number
- CN202411912677.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
The application of existing hydrogels in the field of tissue engineering meniscus is limited by its poor mechanical properties and unstable porous structure. In addition, the incision of traditional meniscus implantation surgery is large and requires suture, resulting in large surgical trauma and long recovery time.
Elastomer/hydrogel composite meniscus scaffold is used to improve the mechanical properties through the elastomer skeleton, and succinimide structure is introduced into the hydrogel matrix to achieve shape memory performance and strong adhesion function, avoiding suture fixation.
It realizes the excellent mechanical properties of the meniscus stent and the retention of porous structure, has shape memory and strong adhesion functions, supports minimally invasive suture-free implantation, and reduces surgical trauma and recovery time.
Smart Images

Figure BDA0005206114130000021 
Figure BDA0005206114130000041 
Figure BDA0005206114130000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of biological tissue engineering scaffolds, and specifically relates to a tissue engineering meniscus scaffold for minimally invasive suture-free implantation surgery, and a preparation method and application thereof. Background Art
[0002] Hydrogels have been widely used in the field of tissue engineering scaffolds due to their good biocompatibility and porous structure. However, due to their high water content, uneven polymer network and lack of effective energy dissipation mechanism, the mechanical properties of hydrogels are usually poor, which affects their application in load-bearing tissues such as tissue engineering meniscus and tissue engineering tendons. An ideal tissue engineering meniscus scaffold should have good mechanical properties, be able to withstand external forces, and protect articular cartilage from external damage. At the same time, it should also have a porous structure to facilitate the transmission of nutrients and the proliferation and growth of cells, and promote the regeneration of new tissues. However, methods to enhance hydrogels, such as double network structure, ion coordination interaction, hydrophobic interaction, organic / inorganic composite, etc., usually make the hydrogel network structure compact, affect the porous structure of the hydrogel, lose the advantages of the hydrogel material, and affect its application in tissue engineering scaffolds. Therefore, how to solve the contradiction between the mechanical properties and porous structure of hydrogels remains a huge challenge. In addition, the current meniscus implant surgery requires a large incision and is mainly fixed by suturing. The surgery is traumatic and takes a long time to recover from the surgery. It also causes secondary damage to the tissue and poses a risk of wound infection. Summary of the invention
[0003] The purpose of the present invention is to provide a tissue engineering meniscus scaffold for minimally invasive suture-free implantation surgery and a preparation method and application thereof.
[0004] The tissue engineering meniscus scaffold for minimally invasive suture-free implantation surgery provided by the present invention is an elastomer / hydrogel composite meniscus scaffold, wherein the elastomer skeleton gives the meniscus scaffold good mechanical properties to withstand external forces to protect articular cartilage, and the hydrogel matrix has a porous structure, which is conducive to the transmission of nutrients and the proliferation and differentiation of cells. At the same time, through the molecular structure design of the elastomer resin, the excellent shape memory performance of the elastomer skeleton and the elastomer / hydrogel composite meniscus scaffold is achieved. By introducing a succinimide structure into the hydrogel resin, a large number of amino groups react with the surface of the biological tissue, strong adhesion is formed to the biological tissue, and the suture-free fixation of the meniscus scaffold is achieved. During the implantation process, a micro incision is cut at the joint, the composite meniscus scaffold is deformed into a long and thin strip, its shape is fixed in a cold water bath, and then implanted into the knee joint through arthroscopic surgery, the meniscus scaffold enters the joint cavity and returns to its original shape at body temperature, and then can be firmly adhered to the joint surface by gently pressing, so as to achieve suture-free fixation.
[0005] The preparation method of the elastomer / hydrogel composite meniscus scaffold provided by the present invention comprises the following steps:
[0006] (1) preparing an elastomeric photosensitive resin, wherein the raw material components of the elastomeric photosensitive resin have the following contents by weight: Polyurethane (meth) acrylate 10-80 parts
[0007] 10~90 parts of light curing diluent
[0008] Photoinitiator 0.1~5 parts
[0009] (2) performing photocuring 3D printing on the elastomer photosensitive resin to obtain an elastomer skeleton having a three-dimensional structure similar to that of a natural meniscus;
[0010] (3) preparing a hydrogel photosensitive resin, wherein the raw material components of the hydrogel photosensitive resin have the following contents in parts by mass:
[0011]
[0012] (4) pouring the prepared hydrogel photosensitive resin into the elastomer skeleton prepared in step (2), and curing the hydrogel resin by ultraviolet light irradiation to obtain an elastomer / hydrogel composite meniscus scaffold.
[0013] In step (1) of the above method, the polyurethane (meth) acrylate is first prepared by reacting a diisocyanate with a hydroxyl-terminated polyester or polyether polyol to obtain an isocyanate-terminated prepolymer, which is then reacted with a hydroxyl-containing (meth) acrylate to prepare a polyurethane (meth) acrylate resin.
[0014] According to an embodiment of the present invention, the diisocyanate is selected from at least one of hydrogenated phenylmethane diisocyanate, isophorone diisocyanate (IPDI), and hexamethylene diisocyanate.
[0015] According to an embodiment of the present invention, the hydroxyl-terminated polyester or polyether polyol is selected from at least one of polycaprolactone diol, polylactic acid diol, polycarbonate diol, polyethylene adipate diol, polybutylene adipate diol, polyethylene glycol, polypropylene glycol, and polytetrahydrofuran diol.
[0016] According to an embodiment of the present invention, the number average molecular weight of the hydroxyl-terminated polyester or polyether polyol is 1000 to 10000 g / mol.
[0017] The hydroxyl-containing (meth)acrylate is selected from at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate and hydroxypropyl methacrylate;
[0018] Furthermore, the polyurethane (meth) acrylate can be prepared according to the following steps:
[0019] S1: In the presence of a catalyst, diisocyanate is mixed with a hydroxyl-terminated polyester or polyether polyol to undergo a stepwise addition polymerization reaction to obtain an isocyanate-terminated prepolymer;
[0020] S2: reacting the isocyanate-terminated prepolymer prepared above with a hydroxyl-containing (meth)acrylate, during which a polymerization inhibitor is added to obtain polyurethane (meth)acrylate.
[0021] According to an embodiment of the present invention, in step S1, the catalyst is a tertiary amine catalyst (such as triethylenediamine, bis(dimethylaminoethyl) ether, etc.) or an organic metal catalyst (such as stannous octoate, n-butyltin dilaurate, bismuth carboxylate, sodium ethoxide, etc.).
[0022] According to an embodiment of the present invention, in step S2, the polymerization inhibitor is selected from at least one of hydroquinone and p-methoxyphenol.
[0023] According to an embodiment of the present invention, in the step S1, the amount of the catalyst is 200 to 600 ppm; the reaction temperature of the polymerization reaction is 50 to 100° C., and the reaction time is 1 to 12 hours.
[0024] According to an embodiment of the present invention, in the step S2, the dosage of the polymerization inhibitor is 50 to 1000 ppm; the reaction temperature of the reaction is 50 to 100° C., and the reaction time is 1 to 12 hours.
[0025] During the preparation of the polyurethane (meth)acrylate, the molar ratio of the diisocyanate, the hydroxyl-terminated polyester or polyether polyol, and the hydroxyl-containing (meth)acrylate is 1: (0.4-0.8): (0.4-1.2).
[0026] In step (1) of the above method, the photocurable diluent is selected from at least one of hydroxyethyl acrylate, isobornyl acrylate, acryloyl morpholine, polyethylene glycol diacrylate, tetrahydrofuran acrylate, and trimethylolpropane triacrylate;
[0027] In step (1) of the above method, the photoinitiator is selected from at least one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)ethylphosphonate, benzophenone, isopropylthioxanthone, 2,4-dimethylthioxanthone, azodimethyl N-2-hydroxybutylpropionamide, azobisisobutyramidine hydrochloride, and phenyl(2,4,6-trimethylbenzoyl)lithium phosphate;
[0028] In step (1) of the above method, the preparation of the elastomeric photosensitive resin comprises the following steps: weighing the polyurethane (meth) acrylate, photocuring diluent, and photoinitiator in proportion, pouring them into a stirrer, and mixing them by mechanical stirring in a light-proof condition.
[0029] In step (1) of the above method, preferably, the raw material components of the elastomeric photosensitive resin have the following contents in parts by mass:
[0030] Polyurethane (meth) acrylate 30-70 parts
[0031] 30-70 parts of light curing diluent
[0032] Photoinitiator 1-3 parts
[0033] In step (2) of the above method, during the photocuring 3D printing, the printing parameters of the 3D printer are set according to the photocuring speed and curing depth of the resin to obtain a model with a smooth surface and high fineness.
[0034] The photocuring 3D printing may be selected from at least one of the following: stereolithography (SLA), digital light processing (DLP), and continuous liquid interface printing (CLIP).
[0035] In step (3) of the above method, the photocurable monomer is selected from at least one of acrylamide, N-isopropylacrylamide, hydroxyethyl acrylate, acrylic acid, methacrylic acid, and N-vinyl pyrrolidone;
[0036] In step (3) of the above method, the photocurable crosslinking agent is selected from at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, N,N-methylenebisacrylamide, waterborne polyurethane acrylate, and waterborne polyurethane methacrylate;
[0037] The succinimide monomer is selected from at least one of acrylate-N-succinimide ester and methacrylate-N-succinimide ester;
[0038] The photoinitiator is selected from at least one of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, azodimethyl N-2-hydroxybutyl propionamide, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide, (2,4,6-trimethylbenzoyl) ethyl phosphonate, benzophenone, isopropyl thioxanthone, 2,4-dimethyl thioxanthone, and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate.
[0039] In step (3) of the above method, the preparation of the hydrogel photosensitive resin includes the following steps: weighing the water-soluble photocurable monomer, photocurable crosslinking agent, succinimide monomer and photoinitiator in proportion, pouring them into a stirrer, and mixing them by mechanical stirring under light-proof conditions.
[0040] In step (3) of the above method, preferably, the raw material components of the hydrogel photosensitive resin have the following contents in parts by mass:
[0041]
[0042] According to one embodiment of the present invention, the mass fractions of each component in the raw material of the elastomeric photosensitive resin are: 40 parts of polyurethane acrylate, 40 parts of isobornyl acrylate, 19 parts of tetrahydrofuran acrylate, and 1 part of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; the mass fractions of each component in the raw material of the hydrogel photosensitive resin are: 12 parts of acrylamide, 3 parts of N,N-methylenebisacrylamide, 4 parts of acrylic acid-N-succinimide ester, 80 parts of deionized water, and 1 part of phenyl(2,4,6-trimethylbenzoyl)lithium phosphate.
[0043] According to one embodiment of the present invention, the mass fractions of each component in the raw material of the elastomeric photosensitive resin are: 70 parts of polyurethane acrylate, 28 parts of acryloylmorpholine, and 2 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; the mass fractions of each component in the raw material of the hydrogel photosensitive resin are: 18 parts of acrylic acid, 2 parts of polyethylene glycol diacrylate, 2 parts of methacrylate-N-succinimidyl ester, 77 parts of deionized water, and 1 part of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.
[0044] In step (4) of the above method, the amount of the hydrogel photosensitive resin is selected based on filling the gaps in the elastomer skeleton.
[0045] In step (4) of the above method, the curing process is: curing with ultraviolet light in a UV box for 10-30 minutes.
[0046] The elastomer / hydrogel composite tissue engineering meniscus scaffold prepared by the above method also belongs to the protection scope of the present invention.
[0047] The present invention also provides application of the elastomer / hydrogel composite tissue engineering meniscus scaffold in the field of biological tissue engineering.
[0048] Compared with the prior art, the present invention has the following advantages:
[0049] (1) The elastomer / hydrogel composite tissue engineering meniscus scaffold provided by the present invention has excellent mechanical properties imparted by the elastomer skeleton and retains the porous structure of the hydrogel matrix;
[0050] (2) The elastomer / hydrogel composite tissue engineering meniscus scaffold prepared by the present invention adopts DLP 3D printing, which has high printing accuracy and can accurately control its bionic three-dimensional structure;
[0051] (3) The elastomer / hydrogel composite tissue engineering meniscus scaffold prepared by the present invention has excellent shape memory performance and strong adhesion function to biological tissues, and can be used for minimally invasive suture-free implantation of tissue engineering meniscus scaffolds;
[0052] (4) The elastomer / hydrogel composite tissue engineering meniscus scaffold prepared by the present invention has excellent articular cartilage protection function. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 Shown is the tensile properties curve of the elastomeric skeleton of Example 1.
[0054] Figure 2 Shown is the shape memory cycle test curve of the elastomeric skeleton in Example 1.
[0055] Figure 3 Shown is the composite meniscus scaffold model prepared by combining an elastomeric skeleton made by DLP 3D printing and a hydrogel.
[0056] Figure 4 What is shown is the shape memory performance of the composite meniscus prepared using the elastomer in Example 1 and the hydrogel photosensitive resin.
[0057] Figure 5 What is shown is the adhesion effect of the hydrogel and elastomer / hydrogel composite meniscus prepared in Example 1 on various biological tissues and natural meniscus.
[0058] Figure 6 The composite meniscus prepared in Example 1 is used in minimally invasive suture-free meniscus implantation surgery.
[0059] Figure 7 What is shown is the in vivo animal experiment verifying the articular cartilage protection function of the composite meniscus prepared in Example 1. DETAILED DESCRIPTION
[0060] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0061] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0062] Example 1. Preparation of elastomer / hydrogel composite meniscus scaffold
[0063] (1) Preparation of elastomer photosensitive resin:
[0064] A preparation method of polyurethane acrylate, the specific steps are as follows:
[0065] Isophorone diisocyanate IPDI (22.2 g, 100 mmol), polycaprolactone diol PCL-2000 (100 g, 50 mmol) and di-n-butyltin dilaurate (0.044 g, 0.2 wt% of IPDI) were added to a flask and reacted at 75 ° C under a nitrogen environment. The reaction was monitored using Fourier transform infrared spectroscopy. When the absorption peak of the isocyanate group no longer changed, the nitrogen was removed and the temperature was lowered to 70 ° C. Then HEA (11.6 g, 100 mmol) and HQ (0.03 g) were added to the flask and reacted in air until the absorption peak of the isocyanate group in the Fourier transform infrared spectrum disappeared, and a transparent viscous liquid was obtained, which was polyurethane acrylate.
[0066] Preparation of elastomer photosensitive resin:
[0067] First, weigh the raw materials according to the formula ratio: the raw material components of the photosensitive resin are calculated by weight as follows:
[0068] Polyurethane acrylate 40 parts
[0069] 40 parts of isobornyl acrylate
[0070] 19 parts of tetrahydrofuran acrylate
[0071] 1 part of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide
[0072] Then, each component is poured into a stirrer in sequence, and mixed by mechanical stirring under light-proof conditions to obtain a photosensitive resin.
[0073] (2) The prepared elastomer photosensitive resin is applied to a DLP 3D printing device to prepare an elastomer skeleton; the printing parameters of the 3D printer are set according to the light curing speed and curing depth of the resin to obtain a model with a smooth surface and high precision.
[0074] (3) Preparation of hydrogel photosensitive resin:
[0075] First, weigh the raw materials according to the formula ratio: the raw material components of the photosensitive resin are calculated by weight as follows:
[0076]
[0077] Then, each component is poured into a stirrer in sequence, and mixed by mechanical stirring under light-proof conditions to obtain a photosensitive resin.
[0078] (4) The prepared hydrogel photosensitive resin was poured into the elastomer skeleton prepared by DLP 3D printing, and cured in a UV curing box for 20 minutes to obtain an elastomer / hydrogel composite meniscus scaffold.
[0079] Example 2: Preparation of elastomer / hydrogel composite meniscus scaffold
[0080] (1) Preparation of elastomer photosensitive resin:
[0081] A preparation method of polyurethane acrylate, the specific steps are as follows:
[0082] IPDI (22.2 g, 100 mmol), PTMG-2000 (160 g, 80 mmol) and bismuth carboxylate (0.089 g, 0.4 wt% of IPDI) were added to a flask and reacted at 80°C under a nitrogen environment. The reaction was monitored using Fourier transform infrared spectroscopy. When the absorption peak of the isocyanate group no longer changed, the nitrogen was removed and the temperature was lowered to 70°C. HEA (4.64 g, 40 mmol) and HQ (0.01 g) were then added to the flask and reacted in air until the absorption peak of the isocyanate group in the Fourier transform infrared spectrum disappeared, and a transparent viscous liquid was obtained, which was polyurethane acrylate.
[0083] Preparation of elastomer photosensitive resin:
[0084] First, weigh the raw materials according to the formula ratio: the raw material components of the photosensitive resin are calculated by weight as follows:
[0085] Polyurethane acrylate 70 parts
[0086] Acryloylmorpholine 28 parts
[0087] 2 parts of ethyl (2,4,6-trimethylbenzoyl)phosphonate
[0088] Then, each component is poured into a stirrer in sequence, and mixed by mechanical stirring under light-proof conditions to obtain a photosensitive resin.
[0089] (2) The prepared elastomeric photosensitive resin is applied to a DLP 3D printing device to prepare an elastomeric skeleton. The printing parameters of the 3D printer are set according to the resin photocuring rate and curing depth to obtain a model with a smooth surface and high precision.
[0090] (3) Preparation of hydrogel photosensitive resin:
[0091] First, weigh the raw materials according to the formula ratio: the raw material components of the photosensitive resin are calculated by weight as follows:
[0092]
[0093] 1 part (2,4,6-trimethylbenzoyl)diphenylphosphine oxide
[0094] Then, each component is poured into a stirrer in sequence, and mixed by mechanical stirring under light-proof conditions to obtain a photosensitive resin.
[0095] (4) The prepared hydrogel photosensitive resin was poured into the elastomer skeleton prepared by DLP 3D printing, and cured in a UV curing box for 20 minutes to obtain an elastomer / hydrogel composite meniscus scaffold.
[0096] Figure 1 The tensile property curve after curing of the elastomer photosensitive resin of Example 1 is shown. The tensile curve of the elastomer shows that its tensile strength is 18.6 MPa, the elongation at break is 415%, and the modulus is 8.4 MPa.
[0097] Figure 2 The shape memory cycle test curve of the elastomer skeleton in Example 1 is shown. The shape memory cycle curve shows that the elastomer has very excellent cycle stability. After 13 cycles of testing, the shape fixation rate of the material is 96.92±0.08%, and the shape recovery rate is 99.96±0.05%, which confirms its excellent shape memory performance.
[0098] Figure 3 The figure shows the composite meniscus scaffold model prepared by the elastomer skeleton made by DLP 3D printing and the composite meniscus scaffold model prepared by compounding with hydrogel. The picture shows that the elastomer skeleton prepared by DLP 3D printing has a three-dimensional structure similar to that of the natural meniscus and a smooth surface, as well as a hollow skeleton structure, indicating that the elastomer resin has excellent printing performance and high printing accuracy. After hydrogel casting and curing, the elastomer / hydrogel composite meniscus scaffold is obtained.
[0099] Figure 4The shape memory performance of the composite meniscus prepared by using the elastomer and the hydrogel photosensitive resin in Example 1 is shown. The deformed composite meniscus can completely recover to its initial shape after being placed in a 37° C. water bath for 6 seconds.
[0100] Figure 5 What is shown is the adhesion effect of the hydrogel and elastomer / hydrogel composite meniscus prepared in Example 1 on various biological tissues and natural meniscus. Figure 5 a) The hydrogel disc has good adhesion to biological tissues, including heart, liver, spleen, lung and kidney. Figure 5 b shows that the hydrogel exhibits strong adhesion to pork tissue when subjected to various deformations such as bending, stretching, and twisting. Figure 5 c shows that the prepared composite meniscus scaffold also has strong adhesion to the sheep meniscus. No shedding phenomenon was observed during bending, stretching and torsion.
[0101] Figure 6 The composite meniscus prepared in Example 1 is used in minimally invasive suture-free meniscus implantation surgery. Figure 6 The process of implanting a meniscus scaffold through arthroscopic surgery is shown in a. The prepared composite meniscus scaffold is twisted into a long and thin strip and its shape is fixed in a cold water bath. The scaffold is then successfully delivered into the joint cavity through the anteromedial entrance. Figure 6 b shows that the meniscus scaffold quickly recovered its original shape in the joint cavity. Subsequently, the scaffold was successfully transferred to the defect site of the medial meniscus using clamps. Figure 6 c shows that the composite meniscus scaffold is firmly fixed on the joint surface after being gently pressed on the joint tissue surface. Even through clamp traction, the composite meniscus scaffold is firmly fixed in the joint tissue.
[0102] Figure 7 The composite meniscus prepared in Example 1 was implanted into the rabbit knee joint to observe the damage of the rabbit knee joint cartilage. Figure 7 a shows that the cartilage surface of the normal group was smooth, only slight cartilage erosion was observed in the transplantation group, while obvious joint degeneration, bone hyperplasia and cartilage erosion occurred in the meniscectomy group. Figure 7 b shows the results of histological evaluation. In the normal group, the articular cartilage was intact and the extracellular matrix structure was normal; in the transplantation group, the articular cartilage was almost intact, with only slight superficial cartilage fibrosis observed; in the meniscectomy group, the superficial cartilage underwent significant degeneration, manifested as severe cartilage fibrosis, cartilage erosion, and degeneration. Figure 7 c shows that the OARSI cartilage degradation score is consistent with the macroscopic and histological findings.
[0103] The elastomer / hydrogel composite meniscus scaffold prepared by the present invention has excellent mechanical properties given by the elastomer skeleton to withstand external forces and protect articular cartilage, while retaining the porous structure of the hydrogel matrix, which is beneficial to cell proliferation and differentiation and promotes tissue regeneration. At the same time, the composite meniscus also has excellent shape memory properties and tissue adhesion function, which can realize minimally invasive suture-free implantation of the meniscus scaffold.
[0104] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.
Claims
1. A method for preparing an elastomer / hydrogel composite meniscus scaffold, comprising the following steps: (1) preparing an elastomeric photosensitive resin, wherein the raw material components of the elastomeric photosensitive resin are as follows in parts by mass: Polyurethane (meth) acrylate 10-80 parts 10~90 parts of light curing diluent Photoinitiator 0.1~5 parts (2) performing photocuring 3D printing on the elastomer photosensitive resin to obtain an elastomer skeleton having a three-dimensional structure similar to that of a natural meniscus; (3) preparing a hydrogel photosensitive resin, wherein the raw material components of the hydrogel photosensitive resin have the following contents in parts by mass: (4) pouring the prepared hydrogel photosensitive resin into the elastomer skeleton prepared in step (2), and curing the hydrogel photosensitive resin through ultraviolet light irradiation to obtain the elastomer / hydrogel composite meniscus scaffold.
2. The preparation method according to claim 1, characterized in that: In the step (1), the polyurethane (meth) acrylate is firstly prepared by reacting a diisocyanate with a hydroxyl-terminated polyester or polyether polyol to obtain an isocyanate-terminated prepolymer; and then reacting with a hydroxyl-containing (meth) acrylate to prepare a polyurethane (meth) acrylate resin; And / or, in the step (1), the photocurable diluent is selected from at least one of hydroxyethyl acrylate, isobornyl acrylate, acryloyl morpholine, polyethylene glycol diacrylate, tetrahydrofuran acrylate, and trimethylolpropane triacrylate; And / or, in the step (1), the photoinitiator is selected from at least one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)ethylphosphonate, benzophenone, isopropylthioxanthone, 2,4-dimethylthioxanthone, azodimethyl N-2-hydroxybutylpropionamide, azobisisobutyramidine hydrochloride, and phenyl(2,4,6-trimethylbenzoyl)phosphate lithium salt.
3. The preparation method according to claim 2, characterized in that: The diisocyanate is selected from at least one of hydrogenated phenylmethane diisocyanate, isophorone diisocyanate (IPDI), and hexamethylene diisocyanate; And / or, the hydroxyl-terminated polyester or polyether polyol is selected from at least one of polycaprolactone diol, polylactic acid diol, polyethylene adipate diol, polybutylene adipate diol, polyethylene glycol, polypropylene glycol, and polytetrahydrofuran diol; and / or, the number average molecular weight of the hydroxyl-terminated polyester or polyether polyol is 1000 to 10000 g / mol; And / or, the hydroxyl-containing (meth)acrylate is at least one selected from hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and hydroxypropyl methacrylate.
4. The preparation method according to claim 2 or 3, characterized in that: The polyurethane (meth) acrylate is prepared according to the following steps: S1: In the presence of a catalyst, diisocyanate is mixed with a hydroxyl-terminated polyester or polyether polyol to undergo a stepwise addition polymerization reaction to obtain an isocyanate-terminated prepolymer; S2: reacting the isocyanate-terminated prepolymer with a hydroxyl-containing (meth)acrylate, during which a polymerization inhibitor is added to obtain polyurethane (meth)acrylate; Preferably, in step S1, the catalyst is a tertiary amine catalyst or an organic metal catalyst; Preferably, in step S2, the polymerization inhibitor is selected from at least one of hydroquinone and p-methoxyphenol; Preferably, in step S1, the amount of the catalyst is 200-600 ppm; the reaction temperature of the polymerization reaction is 50-100° C., and the reaction time is 1-12 hours; Preferably, in step S2, the dosage of the polymerization inhibitor is 50 to 1000 ppm; the reaction temperature of the reaction is 50 to 100° C., and the reaction time is 1 to 12 hours; Preferably, during the preparation of the polyurethane (meth)acrylate, the molar ratio of the diisocyanate, the hydroxyl-terminated polyester or polyether polyol, and the hydroxyl-containing (meth)acrylate is 1: (0.4-0.8): (0.4-1.2).
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step (1), the preparation method of the elastomeric photosensitive resin comprises the following steps: weighing the polyurethane (meth) acrylate, the photocuring diluent, and the photoinitiator in proportion, pouring them into a stirrer, and mixing them by mechanical stirring in a light-proof condition.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In the step (3), the water-soluble photocurable monomer is selected from at least one of acrylamide, N-isopropylacrylamide, hydroxyethyl acrylate, acrylic acid, methacrylic acid, and N-vinyl pyrrolidone; And / or, in step (3), the water-soluble photocurable cross-linking agent is selected from at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, N,N-methylenebisacrylamide, waterborne polyurethane acrylate, and waterborne polyurethane methacrylate; And / or, in the step (3), the succinimide monomer is selected from at least one of acrylate-N-succinimide ester and methacrylate-N-succinimide ester; And / or, in the step (3), the photoinitiator is selected from at least one of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, azodimethyl N-2-hydroxybutyl propionamide, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)ethyl phosphonate, benzophenone, isopropylthioxanthone, 2,4-dimethylthioxanthone, and phenyl(2,4,6-trimethylbenzoyl)lithium phosphate.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (3), the preparation method of the hydrogel photosensitive resin comprises the following steps: weighing the water-soluble photocurable monomer, the photocurable crosslinking agent, the succinimide monomer and the photoinitiator according to a proportion, pouring them into a stirrer, and mixing them by mechanical stirring under light-proof conditions.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In the step (2), the photocuring 3D printing is selected from at least one of the following: stereolithography (SLA), digital light processing (DLP), and continuous liquid interface (CLIP) printing; And / or, in step (4), the curing process is: curing with ultraviolet light in a UV box for 10-30 minutes.
9. An elastomer / hydrogel composite meniscus scaffold prepared by the method according to any one of claims 1 to 8.
10. Application of the elastomer / hydrogel composite meniscus scaffold according to claim 9 in the field of biological tissue engineering.